THE MICROBIAL COMMUNITIES OF SULFUR CAVES: A NEWLY APPRECIATED GEOLOGICALLY DRIVEN SYSTEM ON EARTH AND POTENTIAL MODEL FOR MARS - Boston P.J.; Hose L.D.; Northup D.E.; Spilde M.N. (My University, 2006)
A handful of investigative teams in several parts of the world are studying abundant biological communities in caves formed by sulfuric-acid speleogenesis. These caves are atypical in terms of origin, chemistry, and ecosystem properties. They prominently display sulfur minerals, characteristic cavity topologies, and notable biological diversity and biological productivity resulting directly from the conditions that produce the caves. Even long-inactive systems still harbor some of these indicators. The microbial and macroscopic ecosystems within sulfuric-acid speleogenetic caves are geologically mediated and maintained. This geological mediation is a theme connecting them with other sulfur-driven ecosystems on Earth, including deep-sea hydrothermal vents, sulfurous near-surface hydrothermal systems, and solfataras. Evidence exists for potentially significant microbial participation in the process of speleogenesis itself. Recent results confirming the high relative abundance of sulfur on Mars, an apparent sedimentary basin with high sulfate concentration, near-surface indicators of ice and water, and trace detection of reduced gases (especially methane) in the Martian atmosphere, possibly deriving from subsurface microbial sources, set the stage for suggesting that sulfuric-acid speleogenetic systems may be useful as astrobiological analogs for hypothetical Mars ecosystems. Unique speleogenetic mechanisms may occur on Mars and could provide subsurface void space suitable for habitationby such hypothetical microbial systems. © 2006 Geological Society of America.
Keywords: ACID SPELEOGENESIS; ASTROBIOLOGY; EXTRATERRESTRIAL CAVES; MARS; MICROORGANISMS; SULFUR